Biological effectivenes of colloidal (nanosized) cerium dioxide in Apis mellifera bees - Nikitina, L.; Zasiekin, D.; Zholobak, N.; Efimenko, T.; Odnosum, G.; Postoienko, V. (Scientific Progress & Innovations, 2022)
The paper presents the results of experimental studies on determining the biological effect on bees at oral and contact ingestion of colloidal (nanosized) cerium dioxide (nano-CeO2). The research was carried out based on the laboratory of technological and special measures for the prevention of bee diseases of the National Scientific Center “Institute of beekeeping named after P. I. Prokopovych” and in the laboratory apiary. The drug was used twice in concentrations of 58 mM; 29 mМ; 5,8 mМ; 2,9 mМ with an interval of 7 days during 24 hours with 50% sugar syrup. The body of the bees was also treated twice with aqueous solutions of drugs from a fine-dispersed sprayer on the days of drug feeding. The experimental insects were kept in a thermostat at a temperature of 34–35oC and a relative humidity of 60–70 %. The conducted research found that all of the examined concentrations did not reveal acute toxicity for bees, but concentrations of 58 mМ; 29 мМ; 5,8 mМ accelerated their mortality up to 30 % during feeding (22,88,7 – in the control and 55,315,5 – in the experiment) and up to 40 % – for processing their body (40,014,2 – in the control and 79,211,0 – in the experiment). At the same time, no clear correspondence was observed between the mortality of insects and the concentration of the drug. However, nano-CeO2 in a concentration of 2,9 mМ prolonged the life of bees, which indicates its bio-stimulating effect. The optimal concentration of 2,9 mМ tested under natural conditions for the recovery of bee colonies, in comparison with the “Sterile period for the recovery of bee queen removal” – a technological means that proved to be effective for fungal and bacterial diseases of the bee brood. It was found that feeding bees whit nano-CeO2 at a concentration of 2,9 mМ reduced foulbrood from a high (more than 50 larvae per hive) to a medium degree (10–50 larvae per hive), compared to this indicator of the control group. Creating a sterile period in sick families for the duration of the breeding of new bee queens proved to be an effective measure. Based on obtained results regarding the increase in the survival period of 50% of bees under laboratory conditions of feeding them on sugar syrup together whit colloidal (nano-sized) cerium dioxide in a concentration of 2,9 mМ or lower it is possible to recommend this approach for further research on bee colonies the subject of therapeutic and prophylactic properties for viral, fungal, bacterial diseases of the bee brood.